SMALLHOLDER ARABLE CROP FARMERS’ PERCEPTION OF INTEGRATED SOIL FERTILITY MANAGEMENT IN EGBEDA LOCAL GOVERNMENT AREA OF OYO STATE - ADENIRAN, A. A.; ATERE , A. O; OGUNTADE , M. I; IKUEJAWA , I. I (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2022)
Soil fertility management is one of the key factors for sustainable food production in the agro-system. Fertile soil undoubtedly is required for the efficient performance of crops. The study examined the perception of smallholder arable crop farmers on Integrated Soil Fertility Management (ISFM) in Egbeda Local Government Area of Oyo State. Specifically, the study examined the socio-economic characteristics of the respondents; awareness of ISFM practices, techniques of ISFM adopted and perception of ISFM. One hundred and twenty respondents were drawn using a multistage sampling procedure. Data collection was made using structured and validated questionnaires and analysed with descriptive statistics. Results show that 58.3% of the respondents were male with a mean age of 42 years, having various forms of formal education (75.0%).  Findings also show that 79.2% of smallholder arable crop farmers were aware of the combination of organic manure and inorganic fertilizer. Also, a combination of organic manure and inorganic fertilizer (87.5%) was widely adopted by the farmers. Findings further revealed that smallholder farmers (54.2%) were favourably disposed to integrated soil fertility management. Age (r = -0.123, p = 0.181), household size (r = 0.073, p = 0.426), year of farming experience (r = -0.054, p = 0.556), size of farmland (r = 0.170, p = 0.064) had no significant relationship with farmers’ perception of ISFM. It was concluded that smallholder arable crop farmers were favourably disposed to integrated soil fertility management. There is a need for more information and training on ISFM to further enhance the perception of ISFM. This will go a long way to increase the productivity of the smallholder farming system.